Neutrophil-to-Lymphocyte Ratio Cut-off of > 10,75 as a Predictor of Mortality in Adult Patients with Bacterial Meningitis at Prof. Ngoerah General Hospital - Wandy Margo; Ni M Susilawathi; Anak A A P Laksmidewi; Ketut Widyastuti; I W Widyantara; Anak A R Sudewi (Universitas Kristen Maranatha, 2026)
Pathogenic microorganisms of Mycobacterium tuberculosis cause bacterial meningitis. One in six patients with bacterial meningitis dies, according to WHO (2023). Inflammatory marker neutrophil-lymphocyte ratio (NLR) is easy to measure and inexpensive. The objective of this investigation is to validate NLR >10,75 as a prognostic indicator of mortality in adult patients with bacterial meningitis at Prof. Ngoerah General Hospital. This retrospective cohort observational analytic analysis included 156 patients treated from March 2021 to October 2024. Chi-square bivariate testing and logistic regression using SPSS IBM version 30 will be performed on this research data. After statistical analysis, the research subjects were separated into high and low NLR groups based on ROC of 10.75 and AUC of 79.8%. A study found that NLR >10.75 increases mortality risk in adult patients with bacterial meningitis by 2.842, with a 95% Confidence Interval of 1.871-4.317 and a p-value of <0.001. Bivariate and multivariate analyses indicated that sex, cerebrospinal fluid glucose levels, and NLR significantly affect mortality from bacterial meningitis. This study demonstrated that an NLR value exceeding 10.75 is a predictor of mortality in adult patients with bacterial meningitis at Prof. Ngoerah General Hospital.